Paradoxes of cultural recognition : perspectives from Northern Europe - Alghasi, Sharam, 1966-; Eriksen, Thomas Hylland; Ghorashi, Halleh (Research in migration and ethnic relations series., 2009)
Explicitly comparative in its approach, Paradoxes of Cultural Recognition discusses central issues regarding multiculturalism in today's Europe, based on studies of Norway and the Netherlands. Distinguishing clearly the four social fields of the media, education, the labour market and issues relating to gender, it presents empirical case studies, which offer valuable insights into the nature of majority/minority relationships, whilst raising theoretical questions relevant for further comparisons.